2022
DOI: 10.2478/cee-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dune Sand as Sand Replacement on the Mechanical Properties of the Hybrid Fiber Reinforced Concrete

Abstract: This paper presents an experimental work to study the effect of dune sand as an alternative to sand on the mechanical properties of hybrid fiber reinforced concrete. 24 concrete mixes were prepared, 6 of them without fibers and containing different proportions of dune sand, and 18 concrete mixes with the same proportions of dune sand but containing long and short single and hybrid steel fibers. For the purpose of studying the properties of hybrid concrete, including measuring the workability of fresh concrete,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Dune sand is very fine sand with a maximum particle size of 1.18 mm [ 40 ]. The diameters of more than 90% of its components are between 0 and 0.4 mm [ 41 ].…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Dune sand is very fine sand with a maximum particle size of 1.18 mm [ 40 ]. The diameters of more than 90% of its components are between 0 and 0.4 mm [ 41 ].…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Figure 3 shows the slump flow of concrete with the substitution of dune sand. Dawood et al [ 40 ] reported that the slump flow of concrete decreased with the addition of dune sand. The dune sand particle size distribution is mostly responsible for the decline in a slump.…”
Section: Slump Flowmentioning
confidence: 99%
See 3 more Smart Citations